185k views
2 votes
4(2 - x) + 15 = 3(x + 3)

User Sheen
by
5.4k points

2 Answers

2 votes
4(2-x) + 15 = 3(x + 3)
User Scott Rudiger
by
5.2k points
2 votes

Answer:

x=2

Step-by-step explanation:Simplifying

4(2 + -1x) + 15 = 3(x + 3)

(2 * 4 + -1x * 4) + 15 = 3(x + 3)

(8 + -4x) + 15 = 3(x + 3)

Reorder the terms:

8 + 15 + -4x = 3(x + 3)

Combine like terms: 8 + 15 = 23

23 + -4x = 3(x + 3)

Reorder the terms:

23 + -4x = 3(3 + x)

23 + -4x = (3 * 3 + x * 3)

23 + -4x = (9 + 3x)

Solving

23 + -4x = 9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

23 + -4x + -3x = 9 + 3x + -3x

Combine like terms: -4x + -3x = -7x

23 + -7x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0

23 + -7x = 9 + 0

23 + -7x = 9

Add '-23' to each side of the equation.

23 + -23 + -7x = 9 + -23

Combine like terms: 23 + -23 = 0

0 + -7x = 9 + -23

-7x = 9 + -23

Combine like terms: 9 + -23 = -14

-7x = -14

Divide each side by '-7'.

x = 2

User Priya Rani
by
5.9k points